1997
DOI: 10.1111/j.1651-2227.1997.tb08884.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factors m relation to the serum concentrations of copper and zinc: epidemiological study on children and adolescents in the Spanish province of Navarra

Abstract: This investigation was carried out to show the possible association between groups of children with extreme values of copper and zinc concentrations and cardiovascular risk indicators. Serum copper and zinc concentrations were analysed in a group of 3887 children from Navarra, Spain (both sexes. aged 4-17 years). Hypertension, unfavourable serum lipid profile (total cholesterol, high density lipoprotein cholesterol, low density lipoprotein cholesterol, triglycerides, and cholesterol/HDL and LDL/HDL ratios), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Similar associations between high serum Cu levels and an unfavorable lipid profile were observed in Spanish children and adolescents (28). However, this phenomenon remains poorly understood.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…Similar associations between high serum Cu levels and an unfavorable lipid profile were observed in Spanish children and adolescents (28). However, this phenomenon remains poorly understood.…”
supporting
confidence: 49%
“…Moreover, it is believed that the impairment of this trace element status might be linked to the occurrence of degenerative diseases associated with vascular damage and atherogenesis (24,(26)(27)(28)(29). Previous epidemiological studies on trace element status have been carried out in different European countries, mainly in the central and northern ones (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Several other studies in children or adults have found positive relationships between copper and several forms of cholesterol, 19 HDL cholesterol, 15 or an unfavorable lipid profile (LDL/HDL >2.2). 44 However, other studies among adults report inverse associations between copper and cholesterol 21 or no relationship between copper and triglycerides 15,19,44,45 or cholesterol. 45,46 …”
Section: Discussionmentioning
confidence: 99%
“…There were no significant differences between them and with the NHANES 2011-2014 study (82.7 µg/dL) [49]. However, the mean serum zinc of the three differs significantly from the Navarra study carried out in 3887 children between 4 and 17 years (112.8 µg/dL, p = 0.000) [50] and from the Ortega et al's study performed on 357 Spanish schoolchildren between 8 and 13 years (101.7 µg/dL, p = 0.000) [51]. In the present study, there were few cases with hypozincemia.…”
Section: Discussionmentioning
confidence: 52%